Muslim Progresif dalam Pandangan Islamic World View - Pramono, Agus; Badruddin. Z, M. Badruddin. Z; Yulianto, Rahmat; Sarwanto, Sarwanto; Sumiran, Sumiran (Lembaga Yasin AlSys, 2026)
Although the topic of progressive Muslims has received attention in several previous studies, research that specifically examines how such progressiveness is understood within the framework of the Islamic worldview remains limited. This study aimed to describe the characteristics of progressive Muslims, elaborate their basic conceptual foundations, and explain how progressiveness is understood through the lens of the Islamic worldview. A qualitative approach with a literature-based study design was employed, drawing on various primary and secondary sources from thinkers such as Al-Attas, Abdullah Saeed, and Omid Safi. Data were collected through documentation of books and scholarly journals and were analysed using a descriptive-analytical technique to critically examine the emerging concepts and arguments. The findings indicate that the characteristics of progressive Muslims include critical thinking, an orientation towards social justice, and openness to science and technology while remaining grounded in tauhid. These findings contribute to the development of Islamic worldview theory and broaden understanding of Islamic thought in the modern era. The study concludes that progressiveness can function as a bridge between tradition and modernity that must remain firmly rooted in revelation and the objectives of the law (maqaṣid al-shariʿah), and that it encourages Muslim scholars and educators to integrate modern scientific knowledge with the foundational values of Islam. The implications of this study include a theoretical contribution to enriching the literature on contemporary Islamic thought and practical implications for educational institutions in developing holistic curricula, while also opening avenues for further exploration of the application of progressive values in issues of digital ethics and bioethics.